2014
DOI: 10.5301/hipint.5000142
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hip Geometry after Selective Dorsal Rhizotomy in Children with Cerebral Palsy

Abstract: The results confirm that SDR improves hip geometry as well as function in ambulatory CP children. Long-term studies need to show whether this radiographic improvement has clinical relevance with regard to pain and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Four studies concluded SDR may have a positive effect on hip displacement . Annual change in migration percentage could only be calculated for Floeter et al at −1.7% per year.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Four studies concluded SDR may have a positive effect on hip displacement . Annual change in migration percentage could only be calculated for Floeter et al at −1.7% per year.…”
Section: Resultsmentioning
confidence: 97%
“…Four non‐English language publications that addressed the study question were excluded. After full‐text review, 23 papers remained . A search of the reference lists of these articles and key articles on hip displacement identified one additional article (Greene et al).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations